Organization of the enteric nervous system in the human colon demonstrated by wholemount immunohistochemistry with special reference to the submucous plexus - Wedel, Thilo; Roblick, Uwe; Gleiß, Joachim; Schiedeck, Thomas; Bruch, Hans-Peter; Kühnel, Wolfgang; Krammer, H. (Annals of anatomy, 1999)
To demonstrate the normal topography and structure of the enteric nervous system (ENS) in the human colon, the colonic wall of patients (n = 10, mean age 66.3 years), who underwent abdominal surgery unrelated to intestinal motility disorders, was submitted to wholemount immunohistochemistry. The specimens were stretched out and separated into the tunica muscularis, the outer and inner portion of the tela submucosa and the tunica mucosa. Prior to the application of the neuronal marker Protein Gene Product (PGP) 9.5, the laminar preparations were pretreated with the maceration agent KOH. The plexus myentericus was composed of prominent ganglia and interconnecting nerve fiber strands (NFS) forming a polygonal network, which was denser in the descending than in the ascending colon. Nerve cells were observed within the ganglia as well as in primary, secondary and tertiary NFS. The latter ramified into the adjacent smooth muscle layers, which contained the aganglionated plexus muscularis longitudinalis and circularis. The submucous plexus comprised three nerve networks of different topography and architecture: the delicate plexus submucosus extremus consisted of parallel orientated NFS with isolated nerve cells and small ganglia and was located at the outermost border of the tela submucosa adjacent to the circular muscle layer. The plexus submucosus externus was closely associated with the plexus submucosus extremus and composed of larger ganglia and thicker NFS. The plexus submucosus internus was situated adjacent to the lamina muscularis mucosae and formed a network with denser meshes but smaller ganglia and NFS than the plexus submucosus externus. The NFS of the aganglionated plexus muscularis mucosae followed the course of the smooth muscle cells of the lamina muscularis mucosae. The honeycomb-like network of the plexus mucosus was located within the lamina propria mucosae and divided into a subglandular and a periglandular portion. Single and accumulated nerve cells were observed within the plexus mucosus as a regular feature. The findings confirm the complex structural organisation of the ENS encountered in larger mammals, in particular the subdivision of the submucous plexus into three different compartments. PGP 9.5-immunohistochemistry applied to wholemount preparations comprehensively visualized the architecture of the intramural nerve plexus in human colonic specimens. In addition to conventional cross-sections, this technique allows a subtle assessment and classification of structural alterations of the ENS in patients with colorectal motor disorders.
Elektronische Reproduktion der Druckausgabe
Gesehen am 27.05.2022